Islamic Peace Centered Theology - Machasin Machasin (Universitas Islam Negeri Sunan Kalijaga, 2021)
Although has been so far portrayed as religion of violence, the very essence of Islam is peace. The use of violence in such concepts of jihād (waging holy war) and shahīd (martyr) is actually only allowed in the last resort. Besides, it does not belong to the main precepts of Islam as presented in the arkān al-īmān (the pillars of belief) and the arkān al-islām (the pillars of obligations). This paper argues that peace constitutes the essential part of Islamic theology and that the mission of every human being in Islamic teaching is to be God’s vicegerent on the earth. This mission for a true believer may not be achieved unless he or she works with others in building peace, not by force. Violence can only be used to protect the freedom of as many as members of the community to live peacefully.